PENERAPAN V-NOTCH SEBAGAI INDIKATOR PENAGATURAN AIR PENGENCER CRUDE OIL PADA PABRIK KELAPA SAWIT TANJUNG SEUMANTOH PT. PERKEBUNAN NUSANTARA I - Maisarah; Giyanto; Muhammad Rafli (Institut Teknologi Sawit Indonesia (ITSI), 2022)
V-Notch 900 is a device that has a triangular-shaped gap with an angle of ninety degrees. Tanjung Seumantoh Palm Oil Mill does not yet have a tool to measure the discharge of diluent water used at press stations, so there are often problems with the composition of crude oil that is not ideal due to too much or too little diluent water used. This study aims to determine the magnitude of the effect of using V-Notch as an indicator of crude oil diluent water regulation at Tanjung Seumantoh Palm Oil Mill PT. Nusantara I Plantation so that the comparison after and before Tanjung Seumantoh Palm Oil Mill using V-Notch at the press station is known. The results of this study show that the composition of crude oil before the application of V-Notch is 33:45:22 (Oil:Water:Nos) By using press number 3, 1 and 2 without knowing how much diluent water is used. After the application of V-Notch to 39:40:21 using pressan number 3, 1 and 2, it is known that the amount of diluent water used is 16.2 tons / hour. This indicates that the application of V-Notch can affect the composition of Crude Oil at the Press station to be ideal according to company standards. The oil content in palm fibers and palm kernel is 50%-55% and 40% respectively and the ideal crude oil composition is 40%Oil: 40%Water: 20%Nos.